Diagnostic Accuracy of Barium Enema for the Diagnosis of Hirsch-sprung Disease in Children - Anwar, Zahid; Ahmed, Naveed; Rehman, Shafqat; Afzal, Tamoor; Rehman, Javed-Ur-; Ahmed, Iftikhar (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the diagnostic accuracy of Barium contrast enema for diagnosis of Hirsch-sprung disease, taking histopathology as the gold standard. Study Design: Cross-sectional validation study. Place and Duration of Study: Department of Paediatric Surgery, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Nov 2019 to May 2021. Methodology: A total of 251 patients with symptoms of Hirsch-sprung disease were included. All patients were assessed with a Barium enema and full-thickness rectal biopsy. Barium enema was reported for the presence of contrast in the rectum after 24 hours, the presence or absence of transitional zone and a Recto Sigmoid Index less than 1. Full-thickness rectal biopsy was taken 2 cm above the dentate line, and histopathology was performed to see the ganglion cells in Meissner`s and Myenteric plexus. Results: Histo-pathologically confirmed cases were 120(true positive), where 12(false positive) had no Hirsch-sprung disease on histopathology. In Barium enema negative patients, 113 were true negatives while 06 were false negatives. Overall sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of Barium contrast enema for diagnosis of Hirsch-sprung disease were 95.24%, 90.40%, 90.91%, 94.96% and 92.83%, respectively. Conclusion: We concluded that the diagnostic accuracy of Barium contrast enema for diagnosis of Hirsch-sprung disease is quite high, taking histopathology as the gold standard.